SAT0289 THE INS AND OUTS OF EPIDERMAL DYSFUNCTION IN SYSTEMIC SCLEROSIS (SSC): RESULTS FROM A NOVEL TISSUE ENGINEERED EPIDERMAL EQUIVALENT FROM SSC KERATINOCYTES. (2nd June 2020) - Russo, B.; Borowczyk-Michalowska, J.; Boehncke, W. H.; Brembilla, N.; Chizzolini, C.
Abstract : Background: Skin fibrosis is a hallmark of systemic sclerosis (SSc). It is commonly accepted that vascular damage, immune system activation and, abnormal fibroblasts-to-myofibroblasts differentiation are pathological capital features. Nevertheless, recent evidence portrays a potential role of the epidermis in the pathogenesis of SSc skin fibrosis (1, 2). This new angle on skin fibrosis pathogenesis is particularly attractive as the epidermis is an easy to access therapeutic target. Objectives: To dissect the potential epidermal dysfunction in SSc and its effect on dermis homeostasis, using a novel epidermal equivalent reconstituted from SSc keratinocytes. Methods: Primary keratinocytes and fibroblasts cell lines were generated from skin biopsies obtained from 6 SSc and 6 healthy donors (HD), upon informed consent and ethical approval. Epidermal equivalents (EE) were generated from 4 SSc and 6 HD keratinocytes. Skin and EE expression of the mitotic marker Ki67, of the differentiation markers (K10, involucrin, filaggrin, loricrin), and activation markers (K6, K16) was evaluated by immunohistochemistry. The transcriptomic profile of SSc keratinocytes in monolayer or stratified in EE was identified by RNAseq analysis. EE conditioned medium was used to stimulate fibroblasts. The fibroblast production of interleukin (IL)-6, IL-8, matrix metalloproteinase (MMP)-1, type-I collagen (col-I), and fibronectin was assessed by ELISA. Results: Compared to HD, immunohistochemistry revealed that SSc epidermis is characterized by aberrant premature differentiation and enhanced expression of activation markers associated with a lower mitotic rate of basal keratinocytes. Of interest, EE reconstituted from SSc keratinocytes reproduced most of the abnormalities observed in SSc epidermis. RNAseq analysis revealed that SSc keratinocytes, either cultured in monolayer or in EE, have a distinct transcriptomic profile compared to their HD counterpart, characterized by the downregulation of genes from the HOX family. The supernatant of EE enhanced the production of IL-6, IL-8, MMP-1, col-I, and fibronectin by HD fibroblasts (p<0.05). Except for col-I and fibronectin, this effect was 2-fold higher in the presence of supernatant from EE reconstituted by SSc keratinocytes. Neutralization experiments indicated that IL-1 was, at least in part, responsible for keratinocyte-dependent fibroblasts activation. Conclusion: We established a novel epidermal equivalent tissue engineered from SSc keratinocytes, that recapitulates the in vivo characteristics of SSc epidermis. Our preliminary data suggest that SSc keratinocytes have an intrinsic altered program of differentiation, possibly due to the downregulation of some HOX genes. This altered phenotype is associated with increased production of mediators that stimulate fibroblasts production of inflammatory cytokines. In this scenario, we may hypothesize that SSc epidermis participates in modifying the dermis environment, favoring the development of chronic inflammation and fibrosis. References: [ 1]Takahashi T, Asano Y, Sugawara K, Yamashita T, Nakamura K, Saigusa R, et al. Epithelial Fli1 deficiency drives systemic autoimmunity and fibrosis: Possible roles in scleroderma. J Exp Med. 20317;214(4):1129-51. [2]Nikitorowicz-Buniak J, Shiwen X, Denton CP, Abraham D, Stratton R. Abnormally differentiating keratinocytes in the epidermis of systemic sclerosis patients show enhanced secretion of CCN2 and S100A9. J Invest Dermatol. 2014;134(11):2693-702. Disclosure of Interests: Barbara Russo: None declared, Julia Borowczyk-Michalowska: None declared, Wolf-Henning Boehncke Consultant of: WHB received honoraria as advisor or invited speaker from Abbvie, Almirall, BMS, Celgene, Leo, Lilly, Novartis, UCB., Speakers bureau: WHB received honoraria as advisor or invited speaker from Abbvie, Almirall, BMS, Celgene, Leo, Lilly, Novartis, UCB., Nicolò Brembilla: None declared, Carlo Chizzolini Consultant of: Boehringer Ingelheim, Roche